A method to quantify infection and colonization of holm oak (Quercus ilex) roots by Phytophthora cinnamomi. - Ruiz-Gómez, Francisco J; Sánchez-Cuesta, Rafael; Navarro-cerrillo, Rafael M; Pérez-de-Luque, Alejandro (Plant methods, 2012)
ABSTRACT: Phytophthora cinnamomi Rands. is an important root rot pathogen widely distributed in the north hemisphere, with a large host range. Among others diseases, it is known to be a principal factor in the decline of holm oak and cork oak, the most important tree species in the "dehesa" ecosystem of south-western Spain. Previously, the focus of studies on P. cinnamomi and holm oak have been on molecular tools for identification, functional responses of the host, together with other physiological and morphological host variables. However, a microscopic index to describe the degree of infection and colonization in the plant tissues has not yet been developed. A colonization or infection index would be a useful tool for studies that examine differences between individuals subjected to different treatments or to individuals belonging to different breeding accessions, together with their specific responses to the pathogen. This work presents a methodology based on the capture and digital treatment of microscopic images, using simple and accessible software, together with a range of variables that quantify the infection and colonization process.
Keywords: histology; Holm oak decline; infection degree; Microscopy; Phytophthora; root rot

Changes in pectins and MAPKs related to cell development during early microspore embryogenesis in Quercus suber L. - Ramírez, Carmen; Testillano, Pilar S.; Pintos, Beatriz; Moreno-Risueño, Miguel a; Bueno, María a; Risueño, María C. (European journal of cell biology, 2004)
The occurrence and significance of changes in cell wall components and signalling molecules has been investigated during early microspore embryogenesis in cork oak (Quercus suber L.) in relation to cell proliferation and cell differentiation. Microspore embryogenesis has been induced in in vitro anther cultures of Q. suber by the application of a stress treatment of 33 degrees C. After the treatment, microspores at the responsive developmental stage of vacuolate microspore switched towards proliferation and the embryogenesis pathway to further produce haploid plantlets. Ultrastructural and immunocytochemical analysis revealed changes in cell organisation after induction at different developmental stages, the cellular features displayed being in relation to the activation of proliferative activity and the beginning of differentiation in young and late proembryos. Immunogold labelling with JIM5 and JIM7 antibodies showed a different presence of pectin and level of its esterification in cell walls at different developmental stages. Non-esterified pectins were found in higher proportions in cells of late proembryos, suggesting that pectin de-esterification could be related to the beginning of differentiation. The presence and subcellular distribution of Erk 1/2 MAPK homologues have been investigated by immunoblotting, immunofluorescence and immunogold labelling. The results showed an increase in the expression of these proteins with a high presence in the nucleus, during early microspore proembryos development. The reported changes during early microspore embryogenesis are modulated in relation to proliferation and differentiation events. These findings provided new evidences for a role of MAPK signalling pathways in early microspore embryogenesis, specifically in proliferation, and would confer information for the cell fate and the direction of the cell development.
The following values have no corresponding Zotero field: accession-num: 15346811
Keywords: Cell Differentiation; Cell Differentiation: physiology; Electron; MAPKs; Microscopy; microspore embryogenesis; Mitogen-Activated Protein Kinase 1; Mitogen-Activated Protein Kinase 1: metabolism; Mitogen-Activated Protein Kinase 3; Mitogen-Activated Protein Kinase 3: metabolism; Mitogen-Activated Protein Kinases; Mitogen-Activated Protein Kinases: metabolism; Pectins; Pectins: metabolism; Proliferation; Quercus; Quercus: embryology; Quercus: enzymology; Quercus: metabolism; Seeds; Seeds: cytology; Seeds: ultrastructure

Changes in pectins and MAPKs related to cell development during early microspore embryogenesis in Quercus suber L. - Ramírez, Carmen; Testillano, Pilar S; Pintos, Beatriz; Moreno-Risueño, Miguel a; Bueno, María a; Risueño, María C (European journal of cell biology, 2004)
The occurrence and significance of changes in cell wall components and signalling molecules has been investigated during early microspore embryogenesis in cork oak (Quercus suber L.) in relation to cell proliferation and cell differentiation. Microspore embryogenesis has been induced in in vitro anther cultures of Q. suber by the application of a stress treatment of 33 degrees C. After the treatment, microspores at the responsive developmental stage of vacuolate microspore switched towards proliferation and the embryogenesis pathway to further produce haploid plantlets. Ultrastructural and immunocytochemical analysis revealed changes in cell organisation after induction at different developmental stages, the cellular features displayed being in relation to the activation of proliferative activity and the beginning of differentiation in young and late proembryos. Immunogold labelling with JIM5 and JIM7 antibodies showed a different presence of pectin and level of its esterification in cell walls at different developmental stages. Non-esterified pectins were found in higher proportions in cells of late proembryos, suggesting that pectin de-esterification could be related to the beginning of differentiation. The presence and subcellular distribution of Erk 1/2 MAPK homologues have been investigated by immunoblotting, immunofluorescence and immunogold labelling. The results showed an increase in the expression of these proteins with a high presence in the nucleus, during early microspore proembryos development. The reported changes during early microspore embryogenesis are modulated in relation to proliferation and differentiation events. These findings provided new evidences for a role of MAPK signalling pathways in early microspore embryogenesis, specifically in proliferation, and would confer information for the cell fate and the direction of the cell development.
Keywords: Cell Differentiation; Cell Differentiation: physiology; Electron; MAPKs; Microscopy; microspore embryogenesis; Mitogen-Activated Protein Kinase 1; Mitogen-Activated Protein Kinase 1: metabolism; Mitogen-Activated Protein Kinase 3; Mitogen-Activated Protein Kinase 3: metabolism; Mitogen-Activated Protein Kinases; Mitogen-Activated Protein Kinases: metabolism; Pectins; Pectins: metabolism; Proliferation; Quercus; Quercus: embryology; Quercus: enzymology; Quercus: metabolism; Seeds; Seeds: cytology; Seeds: ultrastructure